Catching fire how cooking made us human - Wrangham, Richard W. 1948- (New York Basic Books, 2010)
In this stunningly original book, renowned primatologist Richard Wrangham argues that "cooking" created the human race. At the heart of "Catching Fire" lies an explosive new idea: The habit of eating cooked rather than raw food permitted the digestive tract to shrink and the human brain to grow, helped structure human society, and created the male-female division of labor.
The cooking hypothesis -- Quest for raw-foodists -- The cook's body -- The energy theory of cooking -- When cooking began -- Brain foods -- How cooking frees men -- The married cook -- The cook's journey -- The well-informed cook.
First published in the United States of America by Basic Books 2009
Keywords: Prehistoric peoples -- Food; Roasting (Cooking) -- History; Fire -- History; Hearths, Prehistoric; Food habits -- History